Determining the host range and metabolic responses to starvation and feeding in a novel outbreak pest of sugarcane, Cacosceles newmannii (Coleoptera: Cerambycidae, Prioninae) - Smit, Chantelle (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScConsEcol)--Stellenbosch University, 2020.